Evaluation of graphene-ferrocene nanocomposite as multifunctional combustion catalyst in AP-HTPB propellant. (15th October 2021) - Zhang, Ming; Zhao, Fengqi; Wang, Ying; Chen, Xueli; Pei, Qing; Xu, Huixiang; Hao, Haixia; Yang, Yanjing; Li, Hui
Graphical abstract: Highlights: A novel graphene-ferrocene nanocomposite G-792-Fe was designed and fabricated successfully. Anchoring on graphene surface can effectively inhibited the migration and volatilization of ferrocene compounds. The AP-HTPB propellant with excellent combustion, anti-migration, safety and mechanical performances was obtained. The performance and mechanism of G-792-Fe in AP-HTPB propellant were analyzed. Abstract: A novel graphene-ferrocene nanocomposite (G-792-Fe) was designed, prepared and characterized systemically using SEM, EDS, FTIR, XPS and RAMAN methods. The as-synthesized G-792-Fe was used as a multifunctional combustion catalyst in ammonium perchlorate-hydroxyl terminated polybutadiene (AP-HTPB) propellant, and the combustion, anti-migration, safety and mechanical performances of AP-HTPB propellant were revealed. The results showed that anchoring on the surface of graphene can effectively inhibit the migration and volatilization of ferrocene compounds in AP-HTPB propellant. The excellent combustion catalytic performance of G-792-Fe on AP-HTPB propellant (burning rate of AP-HTPB propellant containing G-792-Fe increases from 13.87 mm·s −1 to 17.28 mm·s −1 at 15 MPa) is attributed to its positive effect on AP decomposition, which generates more gas-phase products beneficial to the combustion surface thermal feedback and the gaseous REDOX reaction. Additionally, the G-792-Fe presents positive effects on reducing the electrostatic sensitivity and improving the mechanical properties of AP-HTPB propellant. The ignition energy ( E 50 ) and the maximum tensile strength (σm ) of AP-HTPB propellant containing G-792-Fe were increased by 24.4 mJ and 0.75 MPa respectively, compared with AP-HTPB propellant containing catocene (156.8 mJ and 1.26 MPa). The positive effects of G-792-Fe on safety and mechanical performances of AP-HTPB propellant can be due the outstanding electrical and mechanical properties of graphene-based material. Results of this study have implications concerning design and application of multifunctional combustion catalyst, which can improve the combustion performance, anti-migration performance, safety performance and mechanical properties of AP-HTPB propellant.